PENYELESAIAN SENGKETA ANTARA KONSUMEN DENGAN PELAKU USAHA MELALUI MEDIASI DI BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) KOTA DENPASAR - Asri Handayani, I Gst. Ayu; Rai Setiabudhi, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
Economic developments in the field of industry and trade has resulted in a wide variety of goods and/or services. However, consumers are often in a weak position and the result of the indifference most disadvantaged entrepreneurs on product offers. Losses suffered by consumers cause problems or disputes between consumers and business operators, so it is necessary to completion. Dispute settlement can be reached through two efforts, namely through the courts (litigation) and outside the court (non litigation). Efforts outside of court dispute resolution between consumers and business operators conducted by the Badan Penyelesaian Sengketa Konsumen (BPSK). Settlement of Disputes through BPSK, there are several ways (mediation, conciliation, and arbitration) in accordance with the above choice and agreement of the parties to the dispute. The author will discuss one way of resolving disputes through BPSK in Denpasar by way of mediation. Settlement of disputes between consumers and business operators by way of mediation through BPSK is to reach an agreement without prejudice to the parties to the dispute.
Keywords: Out of Court Settlement, Consumer, Business Actor, Mediation